Celiac disease in patient with short stature - Abduljabbar, Hanaa A.; AL-Salami, Rawia M. Y.; Thejeel, Rabab F. (Journal of the Faculty of Medicine Baghdad, 2014)
Back ground: Celiac disease (CD) is an immune–mediated enteropathy induced by gluten with broad spectrum of presentation, many patients with atypical symptoms or clinically silent remain undiagnosed, and are at risk of long-term complications.Objective: The aim of the present study is to determine the of prevalence celiac disease in children with short stature.Patient and Methods: In this prospective study, 307 children 181(58.9%)males and 126(41.1%) females ,with ages ranging from 3 to 17.5years ( mean 12.2 ±3.4) with short statures (height below 3rd percentile adjusted for age and sex) attending the consultation room of endocrinology/ Welfare Teaching Hospital/medical city- Baghdad , were enrolled in this study from the first of Oct 2008 to the first of Aug 2010.Full history, thorough physical examination, immune-biochemical tests ; complete blood count ,renal function tests, serum electrolytes, thyroid function tests, immunoglobulin A and G, tissue transglutaminase (tTG) antibodies , and intestinal biopsy for those with positive celiac serological screens, growth hormone estimation, radiological assessment of bone age, genetic counseling for some females (when available) was done . Each celiac disease case once diagnosed was started on gluten free diet and followed up for one year for growth parameters.Results: celiac disease (CD) was found as the second most common cause of short stature. Unfortunately there was delay in the diagnosis due to asymptomatic status of the disease. Complete catch up in growth had been found in 63.6% after one year of gluten free diet.Conclusion: Celiac disease is an important cause of short stature in children, and should be an essential part of screening panel and workup of short children, irrespective to the presence or absence of gastrointestinal symptoms.